Convertible, transformable and collapsible furniture solutions for cramped city living / Abu Ali, Siti Salwa Isa and Wan Zaiyana Md Yusof - Ali, Abu; Isa, Siti Salwa; Md Yusof, Wan Zaiyana (Research Management Institute (RMI), 2010)
Generally, Collapsible, Convertible and Transformable furniture can provide a creative home decor style while also giving the versatility is usual the first consideration. There are twelve principles of convertible that is useful as theoretical to design collapsible furniture added with the value of convertible and transformable function and purpose. The design of Collapsible, Convertible and Transformable furniture went through three stages of designing process; analysis, synthesis and evaluation or more elementary than this, merely named divergence, transformation and convergence stages. This study is to transform an idea of convertible, transformable and collapsible furniture as a design solution to small space such as low and medium cost of flat and apartment to a final prototype. To externalize the action research process, design methods were chosen as the central to the methodology in this study. Using Observation as Method of Exploring Design Situation, Two-axis Chart as Method of Searching for Ideas, Alexander's Method of Determining Components of Method of Exploring Problem Structure and Selecting Criteria as Method of Evaluation, the results revealed four different designs of Collapsible, Convertible and Transformable were developed and four models-making were built as to be developed for future research by researcher to be commercialized.